Detection of blaOXA-145, blaOXA-224, blaOXA-539, and blaOXA-675 Genes and Carbapenem-Hydrolyzing Class D β-Lactamases (CHDLs) in Clinical Isolates of Pseudomonas aeruginosa Collected from West of Iran, Hamadan - Sezadehghani, Arash; Dehbashi, Sanaz; Tahmasebi, Hamed; Arabestani, Mohammad Reza (International Journal of Microbiology, 2022)
Carbapenem-hydrolyzing class D β-lactamases (CHDLs) are on the rise and are a major public health problem worldwide. Pseudomonas aeruginosa is resistant to carbapenem; currently, the most effective treatment option is being increasingly reported. This study aimed to identify blaOXA-145, blaOXA-224, blaOXA-539, and blaOXA-675 genes in CHDL strains. Samples were collected from clinical specimens admitted to the hospital. Antibiotic susceptibility was determined using the disk diffusion methods. CHDL strains were detected using a phenotypic method (disk diffusion). The PCR method was used to identify blaOXA-145, blaOXA-224, blaOXA-539, and blaOXA-675 genes. Piperacillin-resistant strains (n = 9, 17.4%) had the lowest frequency, and cefoxitin-resistant strains (n = 100, 91.7%) had the highest distribution in P. aeruginosa isolates. Also, 29.35%, 12.8%, and 8.2% were multidrug-resistant, extensively drug-resistant, and pan drug-resistant, respectively. MBL-producing P. aeruginosa and KPC-producing P. aeruginosa were detected, respectively, in 47.7% and 37.6% of isolates. Biofilm formation was observed in 63.3% of P. aeruginosa isolates. The frequency of OXA genes was as follows: blaOXA-145 gene in 30 isolates (27.5%), blaOXA-224 in 24 isolates (22.0%), blaOXA-539 in 22 isolates (20.1%), and blaOXA-675 in 13 isolates (11.9%). However, 19 (17.4%) isolates carry all blaOXA-145, blaOXA-224, blaOXA-539, and blaOXA-675 genes. The antimicrobial resistance and OXA genes among biofilm former strains were significantly higher than those of nonbiofilm former strains (p<0.05). The emergence of carbapenem-resistant isolates of P. aeruginosa has posed serious threats to the community because they exhibit multiple drug resistance, thus limiting the therapeutic options for clinicians.